Bridging different ways of knowing in climate change adaptation requires solution-oriented cross-cultural dialogue - Roos, Roxana; van der Sluijs, Jeroen (Frontiers in Climate, 2025)
The current practices by which knowledge is deployed to inform action on climate change adaptation still privilege a narrow selection of ways of knowing, mainly based on quantification, prediction, certainty and control. We argue that including a wider range of knowledges such as indigenous-, local-, craft-, know-how, tacit-, counter-, gender-dependent-, and experience-based-knowledge, will inform climate solutions better. We explore ways to foster a pluralistic and fair dialogue between diverging ways of knowing in solution-oriented transdisciplinary climate adaptation research. We challenge the assumption that different ways of knowing can and need to be “translated,” “weaved,” “integrated” or “synthesized” to arrive at solutions for climate change adaptation. Such synthesis can often not be done without implying some form of hierarchy between ways of knowing and often reproduces colonial and other power asymmetries while it unduly limits the range of solutions considered. We explore and champion cross-cultural dialogue as an alternative approach to bring incommensurable ways of knowing into dialogical interaction, based on fairness and equality. Instead of aiming at using the end-result of a synthesis across diverging knowledge systems as the primary basis for informing solutions, cross-cultural dialogue starts from the notion that all ways of knowing can be actionable on its own. It seeks to co-create robust solutions that make sense under all relevant ways of knowing considered in a dialogue. We highlight many challenges and pitfalls related to cross-cultural dialogue and stress that participants in transdisciplinary research need to be aware of these.